In-vitro degradation behaviour of starch/EVOH biomaterials - Araújo, M. Alberta (2001)
Blends of corn starch with poly(ethylene–vinyl alcohol) copolymer (SEVA-C) were aged up to 120 days on NaCl sterile isotonic solution (9 g/l) and the degradation solutions were analysed by several techniques. Mechanical properties (i.e. strength, stiffness and ductility), weight loss, and water uptake were also assessed. The evolution of the material structure was followed by scanning electron microscopy (SEM), contact angle measurements and thermogravimetric analysis (TGA). The degradation solutions were monitored with anionic chromatography (HPAE-PAD), colorimetric methods, and Fourier transformed infra-red spectrophotomety (FT-IR) in order to quantify the amount of plasticisers and sugars. SEVA-Cm icrographs presented an increase in the surface porosity as a function of immersion time. The main compound released to the solution is glycerol, the other degradation products are low molecular weight polymeric chains. From the physical–chemical point of view the material degradation is principally associated with the leaching of glycerol, since the other metabolites were not released.